Discovery of novel Asterinaceous black mildew fungi from coastal Maharashtra, India - Natekar, Pratik D.; Bhise, Mahendra R.; Kambhar, Sidanand V. (Phytotaxa, 2025)
Asterinaceous black mildews are ectophytic, obligate biotrophic fungi that parasitize a broad spectrum of angiospermic hosts, including herbs, shrubs, and trees. During recent mycological surveys conducted in the forests of the Ratnagiri and Sindhudurg districts, located in the south-western region of Maharashtra, India, two previously undescribed species of Asterina were identified namely as Asterina thitei sp. nov. and Asterina chandrahasaii sp. nov. These taxa were distinguished from closely related species based on their unique morphological features. Notably, both species possess thyriothecia with stellate dehiscence, a key diagnostic characteristic of the genus Asterina. Comprehensive morphological descriptions, supported by photographic documentation and detailed line drawings, are provided to substantiate their taxonomic placement. This discovery contributes to the growing inventory of Asterinaceous fungi in India and highlights the mycological richness of the Western Ghats region.